2003
DOI: 10.1002/ejic.200300154
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Crystallization Stages of LTA‐Type Zeolite by Complementary Characterization Techniques

Abstract: This paper reports on the physicochemical reorganizations, at 40°C, of a template-free aluminosilicate system yielding an LTA-type zeolite. The events that take place in the system during the transformations of the amorphous material into a crystalline material were monitored by various characterization techniques which provide information from the molecular to the micrometer scale. High-resolution solid-state 29 Si and 27 Al MAS NMR spectroscopy, small-angle X-ray scattering (SAXS), X-ray diffraction (XRD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 28 publications
9
51
0
Order By: Relevance
“…There is no indication from the 29 Si MAS measurements that larger solution-state silicate species, such as secondary building units, may be present, although this does not preclude the existence of a broad distribution of such species that are not resolved. A recent study [47] of the stages of zeolite A crystallization by 29 Si and 27 Al MAS NMR, in combination with small-angle X-ray diffraction, concluded that, during the induction period, reorganization of the amorphous aluminosilica gel takes place, leading to the formation of 'crystalline' zeolite nanoparticles throughout the amorphous gel. These conclusions were based on changes in particle morphology observed in SAXS and TEM measurements that occurred significantly after the onset of local crystallinity, as seen by NMR and wide-angle XRD results.…”
Section: Zeolite Crystallization From Alkaline Solutions and Amorphoumentioning
confidence: 98%
“…There is no indication from the 29 Si MAS measurements that larger solution-state silicate species, such as secondary building units, may be present, although this does not preclude the existence of a broad distribution of such species that are not resolved. A recent study [47] of the stages of zeolite A crystallization by 29 Si and 27 Al MAS NMR, in combination with small-angle X-ray diffraction, concluded that, during the induction period, reorganization of the amorphous aluminosilica gel takes place, leading to the formation of 'crystalline' zeolite nanoparticles throughout the amorphous gel. These conclusions were based on changes in particle morphology observed in SAXS and TEM measurements that occurred significantly after the onset of local crystallinity, as seen by NMR and wide-angle XRD results.…”
Section: Zeolite Crystallization From Alkaline Solutions and Amorphoumentioning
confidence: 98%
“…[33][34][35][36][37][38] On the other hand, there is ample experimental evidence for the presence of an ordered phase in the gel that comprises all structural characteristics of the ultimate zeolite product. [39][40][41][42][43][44][45] These antithetical notions are a consequence of zeolite complexity in both chemistry and morphology. [46,47] A further complication is the fact that there is not a single method of characterization that is able to reveal fully and unambiguously the true nature of the nanoscale events related to zeolite nucleation in gel systems.…”
Section: Introductionmentioning
confidence: 97%
“…They found that the aggregation of the primary colloidal silica particles (5-10 nm) leaded to the formation of 40-80 nm aggregates. Smaihi et al [30] investigated the crystallization stages of LTA zeolite at 40 • C from an organic-free system (the same as the synthesis solution used in our study) by small-angle X-ray scattering (SAXS) and SEM. They found that the primary particles were in the range of 40-100 nm.…”
Section: The Second-stage Synthesismentioning
confidence: 99%